Faktor-faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Laporan Keuangan Pada Koperasi di Kabupaten Gianyar - Darmayanti, Anak Agung Istri Sri Wulan; Diatmika, Putu Gede (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
The growth of active cooperatives in Gianyar Regency tends to decrease every year and the inactive cooperatives experience a relatively large increase. Add to this the annual member meeting at the Gianyar Regency cooperative, which is relatively low. This study aims to determine the effect of accounting information systems, internal control systems, human resource competencies, and organizational commitment to the timely reporting of financial statements in cooperatives in Gianyar Regency. This research was conducted at the Cooperative in Gianyar Regency with a total sample of 148 cooperatives obtained from the Slovin formula. The sampling technique in this study uses proportional cluster sampling technique. This research is a quantitative research sourced from primary data. Data obtained from the distribution of questionnaires to respondents in each Cooperative. The data analysis technique used multiple regression analysis assisted by SPSS version 20. The results showed that the accounting information system, internal control system, human resource competency, and organizational commitment partially had a positive and significant effect on the timeliness of reporting financial statements to cooperatives in Gianyar Regency.